Family presence during resuscitation - Afzali Rubin, Monika (Cochrane Database Syst Rev, 2020)
This is a protocol for a Cochrane Review (intervention). The objectives are as follows: The primary aim of this review is to investigate whether offering relatives the option to be present during resuscitation of patients might lower the occurrence of PTSD‐related symptoms. The secondary aim is to investigate what effect family presence compared to no family presence during resuscitation of patients has on other psychological outcomes of the relatives and on patient morbidity and mortality. We also wish to investigate the effect of FPDR on medical treatment and care during resuscitation. Furthermore, we will investigate and report the personal stress seen in healthcare professionals and if possible describe their attitudes towards the FPDR initiative.